Vaccine applications of flow cytometry - De Rosa, Stephen C. (2012)
Highly effective vaccines have yet to be identified for many widespread infectious diseases including HIV, tuberculosis and malaria. Many vaccine candidates for these diseases have been designed to induce both cellular and humoral immunity, and measurement of the induced cellular immune response and antibody response is critical for monitoring immunogenicity. The flow cytometric intracellular cytokine staining assay is one of the primary assays for enumerating vaccine-induced T cells in vaccine clinical trials. The assay is flexible, allowing for measurement of various cytokines or functions and phenotyping markers, and the assay can be validated. Changes in other cell types such as innate immune cells are monitored by flow cytometric phenotyping assays. Cell sorting of vaccine-induced T cells and B cells is used to allow genomic and transcriptional analysis of these cells. Thus, flow cytometric methods are commonly used in trials testing the next generation of vaccines.